Education and Training on Organic and Inorganic Waste Management for the Community of RT 1 Bunglai Village - Muhammad Syarif; Regista Tri Puspitasari; Nurnajwa Nurnajwa; Nurhanna Rafidah; Agung Waskito (Jurnal Berkala Kesehatan, 2024)
Waste is an environmental problem that requires serious handling. The behavior of the people of Bunglai Village RT 01 towards household waste is based on data, namely by burning it at 44%, throwing it carelessly at 34%, burying it in the ground at 18%, and throwing it into the river at 4%. This community behavior causes environmental pollution and disrupts public health. Thus, intervention is needed at the root of the problem, namely the management of organic and inorganic waste. The intervention carried out was Education and Training on Organic and Inorganic Waste Management. The methods used are Ecobricks and Takakura Compost.The results of the intervention in the community showed that there was an increase in knowledge and attitudes. The average value of the pre-test knowledge was 46.61 to 61.30 at the post-test and the average pre-test attitude score was 15.39 to 17.18 at post-test. To see the output, a pre-test and post-test Wilcoxon test was carried out, it was found that the significance value for knowledge was 0.000<0.05 and for attitude it was 0.000<0.05, meaning that there are differences in knowledge and attitudes  between before and after the intervention in the form of counseling.